Clinic-Level Factors Associated With Retention in Care Among People Living With Human Immunodeficiency Virus in a Multisite US Cohort, 2010–2016. (23rd November 2019) - Oliver, Cassandra D; Rebeiro, Peter F; Shepherd, Bryan E; Keruly, Jeanne; Mayer, Kenneth H; Mathews, W Christopher; Turan, Bulent; Moore, Richard D; Crane, Heidi M; Geng, Elvin; Napravnik, Sonia; Kitahata, Mari M; et al.
Abstract: Background: Retention in care (RIC) leads to reduced HIV transmission and mortality. Few studies have investigated clinic services and RIC among people living with HIV (PLWH) in the United States. We conducted a multisite retrospective cohort study to identify clinic services associated with RIC from 2010–2016 in the United States. Methods: PLWH with ≥1 HIV primary care visit from 2010–2016 at 7 sites in the Centers for AIDS Research Network of Integrated Clinical Systems (CNICS) were included. Clinic-level factors evaluated via site survey included patients per provider/trainee, navigation, RIC posters/brochures, laboratory test timing, flexible scheduling, appointment reminder methods, and stigma support services. RIC was defined as ≥2 encounters per year, ≥90 days apart, observed until death, administrative censoring (31 December 2016), or loss to follow-up (censoring at first 12-month interval without a visit with no future visits). Poisson regression with robust error variance, clustered by site adjusting for calendar year, age, sex, race/ethnicity, and HIV transmission risk factor, estimated risk ratios (RRs) and 95% confidence intervals (CIs) for RIC. Results: Among 21 046 PLWH contributing 103 348 person-years, 67% of person-years were retained. Availability of text appointment reminders (RR, 1.13; 95% CI, 1.03–1.24) and stigma support services (RR, 1.11; 95% CI, 1.04–1.19) were associated with better RIC. Disparities persisted for age, sex, and race. Conclusions: Availability of text appointment reminders and stigma support services was associated with higher rates of RIC, indicating that these may be feasible and effective approaches for improving RIC. Abstract : Among people living with HIV in care at 7 sites in the Centers for AIDS Research Network of Integrated Clinical Systems between 2010 and 2016, clinic-level text appointment reminders and stigma support services were associated with better retention in care.